Analisis resiko likuiditas bank syariah - Indah Susantun; Mustika Noor Mifrahi; Heri Sudarsono (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study attempts to examine the determinants of liquidity risk in Islamic bank by using incorporates several variables that impact the liquidity of Islamic bank. A regression data analysis is conducted on a sample on all of Islamic banks in Indonesia between 2014. 6 and 2019.4. The result show that EQUITY also has a negative relationship with liquidity risk  as a more stable source of funding for Islamic banks tend  a higher ratio of equity lowers liquidity risk.  Then,  SIZE also has a negative relationship with liquidity risk, as larger banks tend customers feel safer dealing with large Islamic  banks. On the other hand, CAR have statistically significant positively relationships with the liquidity risk.  Finally, ROA and FINANCING  are not significance with liquidity risk in Indonesia Islamic Banks